A method for constructing hedge algebraic type-2 fuzzy logic systems - Phong, Phan Anh; Đông, Đinh Khắc; Khang, Trần Đình (Journal of Computer Science and Cybernetics, 2012)
This paper proposed a method for constructing Hedges Algebraic Type-2 Fuzzy Logic Systems (Ha-T2FLSs) from data. This method consist of two main stages. In the first stage, the data-driven Type-1 Fuzzy Logic System (T1-FLS) is design under the combination of Fuzzy C-Means algorithm and Genetic Algorithm (GA). Then we construct Ha-T2FLS on the basis of the above T1-FLS in the second stage. Specifically, we use the rule base of T1FLS as the rule base for Ha-T2FLS and the T1-FLS’s fuzzy sets as the input of Ha-T2FLS. In later stage, the parameters of HaT2FS are optimized by GA. Finally, the experiment on predicting the survival time of myeloma patients has shown the reliable results.